Chance fracture: A case report and review of the literature - Levi Elhadad; Shibin Mathews, MD; Justin Toma, MD; Anjalie Gulati; Daniel Masri, MD (Radiology Case Reports)
A Chance fracture, also known as a “seatbelt fracture,” is “an unstable spinal injury that usually occurs at the thoracolumbar junction. Complications of a Chance fracture include spinal cord injury, neurological deficits, and long-term functional impairment if not promptly identified and treated. In this case report, we present the case of a 13-year-old patient who sustained a Chance fracture following a 30-foot vertical fall, an atypical mechanism of injury. Imaging revealed a vertebral body fracture with a horizontal break through the posterior elements and accompanying ligamentous tears. Management included surgical stabilization via pedicle screw fixation and laminectomy. This case highlights the importance of considering axial loading mechanisms in pediatric trauma patients and the role of timely surgical intervention in preventing long-term complications.